PERBANDINGAN PRESTASI BELAJAR ANTARA SISWA YANG MENDAPATKAN PEMBELAJARAN MATEMATIKA BERBASIS KARAKTER DENGAN KONVENSIONAL - Hilman Yosa Firmansyah; Nitta Puspitasari (Institut Pendidikan Indonesia, 2013)
ABSTRACTIn this paper, we compared two models of learning is a model-based learning and conventional teaching character to see how far these two learning models are instrumental in improving both student achievement or change in the character of students. Researchers want to see whether the learning ability of students get the learning model based character better than those getting conventional model?. Methods that researchers use to determine the extent to which the success of student learning and the changing character of both the gain and the character-based models that get a conventional model